Es posible encontrar un fitoestrógeno para la terapia de reemplazo hormonal, que disminuya el riesgo de cáncer? -- Tema de Proyecto Anillos de Investigación del Programa Bicentenario en Ciencia y Tecnología. - Tchernitch, Andrei N.; Bustamante, Rodrigo; Silvia Erazo; Leonardo Gaete; Garcia, Rubén; Lemus, Igor; Quiñones, Luis; Saavedra, Iván; Villena, Joan (Cuadernos Médico Sociales)
A new research line aimed at the investigation of active agents from Chilean plant species is described. The purpose is to indentify those agents inducing expected pharmacological effects in a hormone replacement therapy in pen- or post-menopausal women, but not increasing, or even decreasing, the risk for development of mammary or endometrial cancer. This possibility is based on previous findings from our research team of a new kind of estrogen receptors, responsible of non-genomic responses to estrogen, and our finding of differences between the classical cytosol-receptor estrogen receptors from the different uterine cell-types. If there exists one kind of estrogen receptors only in the uterus, as it was formerly accepted, then it is not possible to develop the selective estrogenic drug we search for, because all receptors would display the same affinity for this agent;, therefore, it would induce all responses to estrogen stimulation (including those we wish to prevent, such as those presenting risk of cancer development), or would act as antiestrogen, antagonizing all responses to estrogen in the uterus. The existence of multiple and different estrogen receptors, allow the possibility of a dissociation of the various responses, that is, inducing those necessary for therapeutic purposes, but not those adverse effects or responses presenting risk. If a compound with this attributes is found, it allows the possibility of a patent. In this event, our team has the purpose to share the income from the patent (and royalties), between the institutions where this research was performed (including the research team), and those developed the etnomedicinal knowledge without which this research would not be possible, the originary populations. The idea of shared economic benefit is based on the intellectual property right of the originary peoples, proposed by one of us (ANT) at the Sustainable Development Council of Chile, approved unanimously, and sent to the Chilean Senate for law dictation on this matter. These resources should finance promotion and development of the originary people from our country, for instance bilingual schools, research centers for entomedicinal products, or actions to improve their quality of life. This research line was financed by a Research Team Grant in Science and Technology ‘Dissociation of responses to estrogen in the uterus by phytoestrogens, aimed at therapeutics and cancer prevention’, from the Bicentennial Program in Science and Technology, and is in context in the new Government politics to support research subjects contributing to Chilean economical development or to improve the quality of life if its population.